2023
DOI: 10.18488/61.v11i2.3340
|View full text |Cite
|
Sign up to set email alerts
|

School-based practicum and pre-service teachers' self-efficacy: Impact and challenges

Abstract: This study aimed to investigate the effect of school-based practicum experience on the self-efficacy of pre-service teachers (PTs) enrolled in Teacher Education Professional Diploma (TEPD) in Jordanian universities. The study followed mixed methods research. In the quantitative part, an online questionnaire was administered to 134 pre-service teachers (PTs) at the outset of the practicum program. Then it was re-administered to the same sample after completing the practicum. In the qualitative part, semi-struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…The additional pedagogical education, as it was set before the reform (Ministry of Education Youth and Sport, 2019), does not appear to be too effective on this research sample, at least in terms of potentially increasing teacher self-efficacy. Unlike the results from other studies where an increase in self-efficacy after completing educational programs was demonstrated (Altarawneh et al, 2023;Hoy & Spero, 2005;Ross & Bruce, 2010;Thorsnes et al, 2020), self-efficacy did not increase among APE attendees after completion. This result indicates that completing APE did not give them confidence that they could successfully meet the challenges awaiting them in the profession.…”
Section: Discussioncontrasting
confidence: 80%
“…The additional pedagogical education, as it was set before the reform (Ministry of Education Youth and Sport, 2019), does not appear to be too effective on this research sample, at least in terms of potentially increasing teacher self-efficacy. Unlike the results from other studies where an increase in self-efficacy after completing educational programs was demonstrated (Altarawneh et al, 2023;Hoy & Spero, 2005;Ross & Bruce, 2010;Thorsnes et al, 2020), self-efficacy did not increase among APE attendees after completion. This result indicates that completing APE did not give them confidence that they could successfully meet the challenges awaiting them in the profession.…”
Section: Discussioncontrasting
confidence: 80%